Microbial orchestration of neuroimmune crosstalk: from homeostasis to disease - Ouyang, Huixia; Yang, Yang; Zhang, Xiuwei; Cui, Yiyao; Zhang, Yunlei (Frontiers in Immunology, 2025)
The gut-brain-immune axis represents a paradigm shift in understanding systemic homeostasis and disease. While microbial dysbiosis is firmly linked to a spectrum of neurological and immunological disorders, a critical gap persists in our mechanistic understanding of how gut microbes precisely orchestrate the crosstalk between these two systems. This review moves beyond correlation to dissect the causative mechanisms by which microbial metabolites—including short-chain fatty acids, tryptophan derivatives, and neurotransmitters—directly modulate neuroimmune circuits. We synthesize emerging evidence delineating specific molecular circuits that govern microglial maturation, T cell differentiation, and blood–brain barrier integrity, and propose a novel framework for microbiota-mediated neuroimmune regulation. We evaluate cutting-edge microbiota-directed interventions, not merely as generic probiotics, but as precision tools to reestablish neuroimmune homeostasis, thereby outlining a roadmap for next-generation therapeutics in autoimmune, neurodegenerative, and psychiatric diseases.